SARANA DAN PRASARANA DAN IKLIM KERJA DALAM MEMPENGARUHI KINERJA GURU PADA SDN 001 SEKUPANG - Susi Marni,; Julisman,; Nur'aini, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
The purpose of this study was to analyze facilities and infrastructure, work climate in influencing teacher performance at SDN 001 Sekupang. This sampling method uses the sensun method with a total of 43 respondents. This type of research was quantitative, namely by distributing questionnaires which were analyzed using the classical assumption test and multiple linear regression with the SPSS statistical tool. Based on the results of research data processing, it shows that there is an influence of facilities and infrastructure, work climate on teacher performance. And it can be concluded that the variables of facilities and infrastructure and work climate simultaneously affect teacher performance by 60.9% and while the remaining 39.1% is explained by other variables that are not thorough or included in this study